Bathymetric groupings of demersal fishes on the slope and outer shelf at the oceanic side of southern Kuril Islands in spring season - Andrei B. Savin (Известия ТИНРО, 2014)
Abundance and species composition are investigated for demersal fish at the oceanic side of southern Kuril Islands on the data of the bottom trawl survey in the depth range 100-1400 m conducted in the spring of 2009 (for the first time at the continental slope). The total biomass of demersal fish within the surveyed area is estimated as 296.5 thousand tons; besides, 24.15 th. t of walleye pollock Theragra chalcogramma (pelagic species) is accounted at the sea bottom. Three groupings of demersal fishes are identified with different species composition: the upper one at 100-400 m (53.97 th. t, mainly pacific cod Gadus macrocephalus (50.3 %), purplegray sculpin Gymnacanthus detrisus , Steller smallmouth Glyptocephalus stelleri , barred snailfish Crystallias matsushimae , salmon snailfish Careproctus rastrinus , and longjaw rockfish Sebastes alutus ); the medium one at 400-800 m (39.27 th. t, mainly asiatic arrowtooth Atheresthes evermanni (36.6 %), eelpout zesta Bothrocara zestum (19.6 %), aleutian skate Bathyraja aleutica , giant grenadier Albatrossia pectoralis , Matsubara skate B. matsubarai , and alaska skate B. parmifera ); and the most abundant deep one at 800-1400 m (203.34 th. t, basically grenadiers, as giant grenadier (80.5 %), popeye grenadier Coryphaenoides cinereus , and roughscale grenadier C. acrolepis ). Spatial distribution of the mass species is determined by bathymetric range of their habitat: the shelf species concentrate near the shores, and the slope species - in the deep-water trough southeastward from Urup Island. Active spawning is not registered for the demersal species and pollock, possibly because of permanent removing of fish eggs from the upper layer of the surveyed area by the Oyashio Current.